Talking is keep reading: potentialities in flight with the works of Oliver Jeffers in literary actions to (trans)see the world (Olhar de Professor, 2024)
Actively participating in the world requires alteritarian positions and actions from its constituent subjects and it is a fundamental role of Humanizing Education to form people capable of assuming speech positions integrated with the defense of life and Human Rights. In this way, this paper seeks to reflect on the Humanizing potentialities present in literary actions and to dialogue with visual and written statements present in the book Here we are. Notes for living on Planet Earth, by author and illustrator Oliver Jeffers. Thus, this paper aims to motivate ways of (trans)seeing the world through the paths of literary reading.
Keywords: Education; Reading; Humanization